THE STOCK MARKET CHANNEL OF MONETARY POLICY IN EMERGING MARKETS: EVIDENCE FROM THE JAKARTA STOCK EXCHANGE - Anggara, Aang (P2E-LIPI, 2015)
Studies are scant of the stock market channel of monetary policy in emerging markets. I examine the effect of monetary policy on stock returns in the Composite Stock Price Index (IHSG) from 2000Q1 to 2009Q4. This study used the vector autoregression method based on impulse response analysis. The results indicate that the response of the IHSG to growth returns, which are defined by a change in growth of real (M2) money supply and a change of real interest rate of SBI over one month, are negative. Besides that, the change of the IHSG returns respond negatively to changes in inflation. Other results from this study show that changes in the SBI rate over one month are not influential in affecting the stock market sufficiently to enable it to be an instrument of monetary policy.